"Some Corner of a Foreign Field That Is [Not] For Ever England”: Brexit and Poetry - Klepuszewski, Wojciech (Porównania, 2021)
Although it would be absurd to compare the 2016 Brexit referendum and whatever happened in its aftermath to the tragedy of the Great War, surprising as it may seem, the two have something in common. This is so because the 1914–1918 period triggered a flood of poetry, written not only by established literary figures, but also by thousands of civilians who found it a means of expressing their emotions. By the same token, the post-referendum years produced a poetic response on the part of ordinary citizens. This article tries to take a closer look at how once again British citizens turn to poetry to voice their fears and frustration.